Mobile-based Hospital Bed Management with Near Field Communication Technology : A Case Study - Lam, M. C.; Ayob, M.; Lee, J. Y.; Abdullah, N.; Hamzah, F. A.; Zahir, S. S. M. (Engineering, Technology & Applied Science Research, 2020)
Bed management is one of the most crucial tasks in a hospital. A desktop-based (PC) information technology system has been widely adopted to assist this operation. The fixed location and the limited amount of available PCs shared among staff for different routine tasks can cause delays in bed information updating and therefore delays to the bed management processes. With the penetration of smartphones, a mobile-based application becomes a reliable alternative solution for bed management to complement the existing system. Smartphones offer a few benefits, especially mobility because users can update the information from any place and at any time. Our aim was to study the applicability of a mobile-based application for assisting bed management operation. The application consisted of ward-based bed information visualization, bed information updating, and ward information updating modules. Observation and interviews with expert users were performed to outline the required functions of the application. On a Likert 1-5 scale, the mobile application achieved a mean score of 3.45 for usefulness, 3.40 for ease of use, and 3.42 for satisfaction. Meanwhile, the respondents were also concerned about the mobile data consumption of the app, which took up 45.8% of the negative feedback. On the positive side, the respondents agree that the mobile application helps them in the bed management operation.